Evaluación de tratamientos herbicidas preemergentes y postemergentes en el cultivo de arroz de riego, en la zona de Babahoyo - Vargas Benítez, William Alfredo. (2013)
This experimental study was conducted in the grounds of the farm " San Pablo " belonging to the Faculty of Agricultural Sciences , Technical University of Babahoyo , located 7.5 km road Babahoyo - Montalvo , Rivers Province . The planting was irrigated using INIAP 15. The aim of this work was to : assess the compatibility of mixtures of herbicides pre emergent and post emergent ; identify the best treatment and subtratamientos for growing rice and economically analyze the results. Pre- emergent herbicides were investigated Pendimentalin , butachlor , Gamit , benthiocarb , Oxadiazon , butachlor in admixture with postemergence Metsulfuron methyl + bispyribac sodium , Cyhalafop + penoxulam , and propanil + Pyribenzoxim applied in blends. Experimental design was used " Divided Plots " with three pre emergent herbicide treatments and three postemergence herbicide sub-treatments with three replications.............